Uropathogen Antibiotic Resistance in Adult Women Presenting to Family Physicians with Acute Uncomplicated Cystitis. Issue 5 (1st October 2004) - McIsaac, Warren J; Mazzulli, Tony; Moineddin, Rahim; Raboud, Janet; Ross, Susan
Abstract : BACKGROUND: Increasing rates of trimethoprim-sulfamethoxazole (TMP-SMX) resistance among uropathogens have raised concerns about its continued role in empirical treatment of acute uncomplicated cystitis in adult women. OBJECTIVES: To determine current rates of antibiotic resistance among uropathogens in the community. METHOD: Urine culture reports from adult women with symptoms of cystitis attending the offices of family physicians from across Canada were examined. Antibiotic sensitivities and the total number of antibiotics an organism was resistant to was determined. RESULTS: In 446 women, 235 (61.4%) positive urine cultures were identified. Of these, 38.2% were resistant to at least one antibiotic and 21.5% were resistant to two or more antibiotics. The rate of ampicillin resistance was 34.1%. For TMP-SMX, resistance was reported in 10.8% of samples. Antibiotic resistance was higher in British Columbia (55%) and western provinces (48%), compared with Ontario (33.3%) and the eastern provinces (26.3%, P=0.04, Fisher's exact test). Multidrug resistance was also higher in western Canada (33.9%) than in eastern Canada (16.6%, P=0.007). CONCLUSIONS: TMP-SMX resistance in Canada remains within current recommended guidelines, allowing for its continued use as a first line empirical treatment for acute cystitis in adult women. The reasons for higher rates of antibiotic resistance in western Canada merit further study.